Toxicological Assessment of Bromochlorophene: Single and Repeated-Dose 28-Day Oral Toxicity, Genotoxicity, and Dermal Application in Sprague–Dawley Rats - Won, Hansol; Jeong, Da Hye; Shin, Hyo-Sook; Lee, Jin Hee; Lee, Jeong Pyo; Yang, Jun-Young; Jung, Kikyung; Jeong, Jayoung; Oh, Jae Ho (Frontiers in Pharmacology, 2021)
Bromochlorophene (BCP) has shown good properties in sterilization and antibacterial activity and widely used as a household chemical. We evaluated the genotoxicity, single and repeated dose 28-days oral toxicity, and dermal application of a BCP suspension in Sprague–Dawley (SD) rats. For the single-dose toxicity study, a dose of 25-1,000 mg per kg of bodyweight (mg/kg b.w.) of BCP was given once orally SD rats. Mortality and clinical signs were observed and recorded for the first 30 min after treatment, at 4h post-administration and then at least once daily for 14 days after administration. For the repeated dose 28-day toxicity study, the high dose was set as 1,000 mg/kg b.w. and the middle, middle-low, and low dose were set to 500 mg/kg, 250 mg/kg and 125 mg/kg, respectively. Haematology and biochemistry parameters were examined. Gross pathologic and histopathologic examinations were performed on selected tissues from all animals. Bacterial reverse mutation assay, in-vitro chromosomal aberration assay and in-vivo micronucleus assay were performed to assess genotoxicity - dermal application exposure assessment of BCP in rats. A high oral approximate lethal dose (ALD) of 1,000 mg/kg was observed in the single-dose toxicity test. During the repeated dose 28-day time period, most animal deaths after administration during the first 3 weeks. The 1,000 mg/kg b.w. oral dose caused the death of six male rats (6/7) and four female rats (4/7). At the 500 mg/kg b.w., the female rats showed mortality (1/7). For biochemistry assays, cholesterol was increased significantly compared to vehicle in both sexes in the 250 mg/kg and 500 mg/kg groups. Histopathological changes with treatment-related finding were observed pancreas in female treated with a high dose of BCP compared with the vehicle group. BCP has assessed no genotoxic effect. These data suggested that the ALD of BCP, estimated as a non-genotoxic substance, was over 1,000 mg/kg b.w. in the single-dose toxicity study, and the NOAEL of BCP was considered to 250 mg/kg b.w. for male and female rats after repeated oral administration for 28-day under the present study conditions.